Evaluation of Some Heavy Metals, Their Fate and Transportation in Water, Sediment, and Some Biota within AL-Musayyib River, Babylon Governorate, Iraq - Jasim Mohammed Salman; Ashwak Falih Kaizal; Patryk Kot (مجلة بغداد للعلوم, 2023)
This study estimated seven heavy metals (Fe, Cu, Zn, Pb, Ni, Cd, Cr) in water (dissolved and particulate phase), sediments and some aquatic organisms including two species from aquatic plants (Ceratophyllum demersum&Phragmites australis); one species of clam (Psedontopeses euphratics) and two species from fish (Oreochromis aureus& Leuciscus vorax)in four sites within Mashroo AL- Musayyib channel project/ branch  of Euphrates river, Babylon , medial of Iraq . This aims to show the concentration of these elements, their fate and the mechanisms of their transmission through the food chain in this lotic aquatic system ; also in addition to examining  some physicochemical properties of river water such as water temperature (WT),air temperature (AT),pH , electrical conductivity ( EC) , salinity ,total dissolved solid ( TDS), total  solid  suspended (TSS) , dissolved oxygen (DO)  and biological oxygen demand ( BOD5) .The occurrence in heavy metals in water was found in the order in the Dissolved phase :- Zn> Fe > Cu> Ni>Pb> Cr > Cd, the zinc element recorded the highest rate in site two for spring season while the cadmium element recorded the lowest rate in site one for spring season. In the particulate phase:- Zn> Cu >Fe > Ni>Pb> Cr > Cd,  the zinc element recorded the highest rate in site two for spring season while the cadmium element recorded the lowest rate in site four for spring season. The sediment order was Zn> Cu >Fe >Pb> Ni > Cd > Cr where the zinc element recorded the highest rate in site two for spring season where as the chromium element recorded the lowest rate in site two for spring.  In aquatic plant the order was in C. demersum :Zn> Fe > Cu>Pb> Cr > Ni > Cd,  the zinc element recorded the highest rate in site four  for winter season while the cadmium element recorded the lowest rate in site one for autumn season.  In P. australis: Zn> Fe > Cu>Pb> Cd > Ni > Cr , the zinc element recorded the highest rate in site two for spring  season while the chromium  element recorded the lowest rate in site two for spring season. In clam the order was: Zn> Fe > Cu> Ni >Pb> Cd > Cr where the zinc element recorded the highest rate in site two for spring season while the chromium recorded the lowest value in site 3 through  winter 2021.In fish species (O. aureas) the order was Fe > Zn > Cu>Pb> Cr > Cd > Ni. The iron element recorded as the highest rate in site 2 in spring 2021 whilethe element that recorded the lowest rate was Ni in site 2for spring in L. vorax. The iron element recorded the highest rate in site one for summer season where as the Nickel was recorded a lower value in site four in spring2021.